The impact of the COVID-19 Pandemic on labor migrants in Argentina - Pizarro, Cynthia Alejandra (2020)
The paper presents some data of a sociological survey of migrants in Argentina after the outbreak of the COVID-19 Pandemic. It is noted that after the introduction of restrictive measures, the situation of migrants has worsened significantly. Migrants indicated cramped living conditions, limitedaccess to medical care, job loss, and a significant reduction of income as the main problems they have faced. One of the biggest challenges for Argentina is the informal employment of migrants.The complication of bureaucratic procedures has led to the fact that many migrants cannot complete the necessary documents on time. During the pandemic such migrants are at risk because many of them lost their jobs and are unable to pay for housing, to receive medical care, to buy food, while those who continue to work are at risk of infection. The Government of Argentina attempts to support people during the pandemic, including some categories of migrants. However,some migrants find themselves in a position of social exclusion, as the state support measures do not apply to them, and they also cannot return to their home country due to border closures. The article also observes a significant decline in migrant remittance flows.